Bitcoin: an open source currency and more (Journal of Open Law, Technology & Society, 2018)
The emergence of a cryptocurrency in the digital domain went unnoticed for years until the general press started to cover Bitcoin's more than tenfold raise in price in the space of a few months in 2017. Earlier on, technical and legal discussion revolved around one of its fundamental building blocks, but Bitcoin is more than the blockchain or an investment object. It is a revolutionary open source artefact that is bound to change the way we consider currency, as well as a proof-of-concept for how parts of international trade could disfranchise banks and other institutions as payment service providers.